Relação família, escola e aprendizado no período da pandemia: o que dizem as famílias? - Silva, Rute Santos da (Brasil, 2023)
The present work is entitled “relationship family, school and learning process during the pandemic: what do families say”? The initiative for choosing the theme was from the moment I started doing internships in schools, during the COVID 19 pandemic, in the years 2020 and 2021, where classes were being taught at home. We are guided by the following question: how parents managed/or failed to help their children by reconciling their children's studies with work, and the difficulties they had during isolation. Based on this question, we are guided by the following objective: to analyze the participai-o of parents in the literacy process during the pandemic. As a basis we leaned on the studies of Leal (2005) Parolin,2008, Teberosky and Gallart (2004) and on the legislation: Federal Constitution (1988), Law of Guidelines and Bases of National Education (1996) and the Statute of the Child and Adolescent (nineteen ninety). It was based on a qualitative approach, with a descriptive approach and a case study. We used the questionnaire with parents as a tool for data construction. The results point to difficulties and limitations in the participation of parents in activities, the importance of teacher mediation and the impairment of learning during the pandemic.